Post-sinter annealing influences on coercivity of multi-main-phase Nd-Ce-Fe-B magnets. (March 2018) - Zhang, Yujing; Ma, Tianyu; Yan, Mi; Jin, Jiaying; Wu, Bo; Peng, Baixing; Liu, Yongsheng; Yue, Ming; Liu, Chuyang
Abstract: Post-sinter annealing (PSA) plays an essential role on enhancing coercivity of the single-main-phase (SMP) Nd2 Fe14 B-based magnets due to the formation of continuous Nd-rich grain boundary (GB) layers to decouple the adjacent grains. Here we investigated the PSA effects on coercivity of the multi-main-phase (MMP) [(Nd, Pr)0.55 Ce0.45 ]30.5 Febal M1.0 B1.0 (wt.%) magnet prepared by sintering the mixture of Ce-free and Ce-containing 2:14:1 powders, which has shown superior magnetic properties to the SMP one at the same average composition. The annealing temperature dependent investigation showed that the coercivity can be enhanced when annealing at low temperatures, but becomes even lower than that of the as-sintered state when annealing at higher temperatures, despite that continuous RE-rich GB layers are formed after annealing. When raising the annealing temperature, the RE gradients within the 2:14:1 phase grains are reduced to reach the ''close to equilibrium (or SMP)'' state due to the further elemental inter-diffusions among the Ce-lean and Ce-rich 2:14:1 grains, which weakens the magnetic impedance effect among them. These findings suggest a unique clue to enhance coercivity of the MMP RE-Fe-B magnets by PSA, i.e. the competitive contributions between the formation of continuous GB layers and the gradual chemical homogenization should be balanced. Graphical abstract: Nonlinear annealing temperature dependent coercivity for the MMP Nd-Ce-Fe-B magnet (a) due to the gradually homogenized RE distributions within the 2:14:1 phase grains (b and c) that offsets the positive contribution from the formation of continuous grain boundaries. Image 1